2022
DOI: 10.1021/acs.jnatprod.1c00805
|View full text |Cite
|
Sign up to set email alerts
|

Target-Based Virtual Screening and LC/MS-Guided Isolation Procedure for Identifying Phloroglucinol-Terpenoid Inhibitors of SARS-CoV-2

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to more than 5 million deaths worldwide to date. Due to the limited therapeutic options so far available, target-based virtual screening with LC/MS support was applied to identify the novel and high-content compounds 1 – 4 with inhibitory effects on SARS-CoV-2 in Vero E6 cells from the plant Dryopteris wallichiana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…SPR is an efficient approach for drug discovery. Hou et al used SPR to evaluate the antiviral activity of novel phloroglucinol-terpenoid against SARS-CoV-2 M pro [ 8 ]. We assessed the direct binding affinities between the 12 catechin derivatives and M pro by analyzing their equilibrium dissociation constants (K D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPR is an efficient approach for drug discovery. Hou et al used SPR to evaluate the antiviral activity of novel phloroglucinol-terpenoid against SARS-CoV-2 M pro [ 8 ]. We assessed the direct binding affinities between the 12 catechin derivatives and M pro by analyzing their equilibrium dissociation constants (K D ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, non-peptidic inhibitors inactivate the M pro by forming covalent, hydrogen, and hydrophobic bonds. For example, phloroglucinol-terpenoids have vital interactions with SARS-CoV-2 M pro , including hydrogen bonds, hydrophobic bonds, and the spatial occupation of the B ring [ 8 ]; the pyrogallol moiety of myricetin covalently binds with the –SH group and modifies the catalytic cysteine as an electrophile warhead [ 9 ]; proanthocyanidins and pentagalloylglucose as natural polyphenols have potential antiviral activity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compound 30 was virtually screened on AutoDock 4 to see the binding interactions between the ligand and amino acid residues of 3CL pro . It was noted that Compound 30 formed H-bonds with MET165, ASN142, GLU166, and GLN192 and hydrophobic interactions with PHE140 [ 52 ]. Kim et al (2022) identified the antiviral potential of mulberrin (kuwanon C) 31 ( Figure 5 ), isolated from the commonly known mulberry plant.…”
Section: In Vitro and In Silico Studiesmentioning
confidence: 99%
“…Thus, these compounds represent new and potential lead compounds for the development of anti-SARS-CoV-2 drugs. 44 Chemical investigations on the plant Cannabis sativa (Cannabaceae) led to the isolation of cannabisol ( 64 ), the first example of methylene-bridged dimeric cannabinoid. 45 In 2020, cannabitwinol ( 65 ), the second member of methylene-bridged dimeric phytocannabinoids, was isolated from hemp ( Cannabis sativa L.) industrial extract.…”
Section: Naturally Occurring Methylene-bridged Dimersmentioning
confidence: 99%